Analysis of wind velocity and release angle effects on discus throw using computational fluid dynamics - Rouboa, Abel I (2013)
The aim of this paper is to study the aerodynamics of discus throw. A comparison of numerical and experimental performance of discus throw with and without rotation was carried out using the analysis of lift and drag coefficients. Initial velocity corresponding to variation angle of around 35.5° was simulated. Boundary condition, on the top and bottom boundary edges of computational domain, was imposed in order to eliminate external influences on the discus; a wind resistance was calculated for the velocity values of 25 and 27 m/s. The results indicate that the flight distance (D) was strongly affected by the drag coefficient, the initial velocity, the release angle and the direction of wind velocity. It was observed that these variables change as a function of discus rotation. In this study, results indicate a good agreement of D between experimental values and numerical results.